The Role of Psychological Capital on the Effect of High-Performance Work System and Proactive Personality on Job Performance - Alvin Permana Emur; Handwita Mufidawati; Muhammad Futtuwah Andryadi; Elok Savitri Pusparini; Riani Rachmawati (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to investigate the effect of a high-performance work system (HPWS) and proactive personality on job performance and examine the role of psychological capital as mediation in the proposed research model. Design/Methods/Approach: This study adopts quantitative approaches by distributing cross-sectional surveys of multi-sector employees; 231 respondents were collected. The data collected underwent model evaluation and structural equation modeling using Smart PLS 3.2.9, employing the embedded two-stage approach. Findings: The statistical analysis indicates that High-Performance Work Systems (HPWS) and proactive personality directly impact job performance. Moreover, they also have an indirect positive impact through mediation by psychological capital. Originality: This study contributes to the existing literature by investigating the mediating role of psychological capital on the influence of HPWS and proactive personality on job performance in the context of workers in various industrial sectors in Indonesia. This study confirms that HPWS, proactive personality, and psychological capital positively impact employee job performance. It also supports the broaden-and-build theory of positive emotions and the JD-R model in Indonesian workplaces. Practical/Policy implication: The findings of this study can provide valuable insights, evidence, and knowledge to academics and Human resource managers. By implementing High-Performance Work Systems (HPWS), recruiting workers with a proactive personality, and improving employee job performance, organizations can build a solid human resource base that can contribute to achieving optimal organizational goals. Human resource managers are advised to develop policies that focus on recruitment, training, motivation, and enhancing opportunities while fostering a proactive personality among employees. It will encourage optimism, hope, resilience, and efficacy in performing tasks, improving organizational performance and outcomes.